Demo: DeLorean: Using Speculation to Enable Low-Latency Continuous Interaction for Mobile Cloud Gaming - Wolman, Alec; Cuervo, Eduardo; Chu, David; Kopf, Johannes (MobiSys 2014, 2016)
Playing games on mobile devices is very popular. Recently, cloud gaming – where datacenter servers execute the games on behalf of thin clients that merely transmit UI input events and display output rendered by the servers – has emerged as an interesting alternative to traditional client-side game execution. Cloud Gaming-as-a-Service (GaaS) offers several advantages salient to mobile clients. First, users with low end devices can get the same high quality experience as users with high end devices. Second, mobile game developers avoid two challenges that arise with the huge diversity of mobile devices: platform compatibility headaches and per-platform performance tuning. Third, upgrading servers (e.g., for bug fixes, game updates) becomes far easier than redeploying new software to clients. Finally, players can select from a vast library of games and instantly play any of them.